Gender differences in STEM persistence after graduation - Judith Delaney; Paul J. Devereux (University College Dublin, UCD School of Economics, 2022)
Much attention is focused on finding ways to encourage females to study STEM in school and college but what actually happens once women complete a STEM degree? We use the UK Quarterly Labour Force Survey to trace out gender differences in STEM persistence over the career. We find a continuous process whereby women are more likely to exit STEM than men. Among holders of STEM undergraduate degrees, women are more likely to obtain a nonSTEM master's degree. Then, after entering the labour market, there is a gradual outflow of females during the first 15 years post-graduation so that females are about 20 percentage points less likely to work in STEM compared to their male counterparts. Conditional on leaving STEM, we find that females are more likely to enter the education and health sectors while males are more likely to enter the more lucrative business sector and that this can partly explain the gender pay gap for STEM graduates. Overall, our results suggest that policies that aim to increase the proportion of females studying STEM in school and college may have less effect than expected due to the lower attachment of females to STEM after graduation. Such policies may need to be augmented with efforts to tackle the greater propensity of females to exit STEM throughout the career.
Keywords: I23; I26; J16; J24; J31; 330; STEM; gender; STEM gender gap; labour market; gender pay gap